Cognitive function in the oldest old: women perform better than men. Issue 1 (1st July 2001) - van Exel, E; Gussekloo, J; de Craen, A J M; Bootsma-van der Wiel, A; Houx, P; Knook, D L; Westendorp, R G J
Abstract : OBJECTIVE: Limited formal education is associated with poor cognitive function. This could explain sex differences in cognitive function in the oldest old. Whether limited formal education explains differences in cognitive function between elderly women and men was explored. METHODS: The Leiden 85-plus Study is a population based study investigating all 85 year old inhabitants of Leiden with an overall response rate of 87%. A sample of 599 participants were visited at their place of residence. The mini mental state examination was completed by all participants. Cognitive speed and memory were determined with four neuropsychological tests in participants with a mini mental state examination score higher than 18 points. RESULTS: The proportion of women with limited formal education was significantly higher than that of men (70% v 53%, p=0.001), but women had better scores for cognitive speed and memory than men (p<0.05). After adjustment for differences in limited formal education and the presence of depressive symptoms, the odds ratio for women to have a higher cognitive speed than men was 1.7 (95% CI; 1.0 to 2.6), and for them to have a better memory the odds ratio was 1.8 (95%CI; 1.2 to 2.7). CONCLUSION: Women have a better cognitive function than men, despite their lower level of formal education. Limited formal education alone, therefore, cannot explain the differences in cognitive function in women and men. These findings support the alternative hypothesis that biological differences, such as atherosclerosis, between women and men account for the sex differences in cognitive decline.